2008
DOI: 10.1590/s1676-06032008000100020
|View full text |Cite
|
Sign up to set email alerts
|

Ocorrência e caracterização de galhas de insetos em áreas de restinga de Bertioga (São Paulo, Brasil)

Abstract: Maia, V. C.; Magenta, M. A. G.; Martins, S. E. Occurrence and characterization of insect galls at restinga áreas of Bertioga (São Paulo, Brazil). Biota Neotrop., vol. 8, no. 1, Jan./Mar. 2008. Available from .Abstract: Studies on entomogenous galls at restinga areas in the State of São Paulo are very scarce, and the diversity of galling insects is completely unknown in these areas. In this study, we investigated restinga environments … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
87
0
29

Year Published

2011
2011
2014
2014

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 103 publications
(129 citation statements)
references
References 21 publications
(10 reference statements)
13
87
0
29
Order By: Relevance
“…This result corroborate another data reported in other major studies in the literature, those indicates 58% of galls induced by Cecidomyiidae, according to Maia et al (2008), 54% Urso- Guimarães et al (2006), and 93%, according to Fernandes & Negreiros (2006), demonstrating the importance of the family in community of gall makers.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…This result corroborate another data reported in other major studies in the literature, those indicates 58% of galls induced by Cecidomyiidae, according to Maia et al (2008), 54% Urso- Guimarães et al (2006), and 93%, according to Fernandes & Negreiros (2006), demonstrating the importance of the family in community of gall makers.…”
Section: Discussionsupporting
confidence: 92%
“…The fact that 75% of the galls have been found in leaves, corroborate the pattern found in studies in Brazil, that indicates the leaf as organ most commonly attacked by gall makers (Maia et al 2008, Maia 2001, Urso-Guimarães et al 2003, Fernandes & Negreiros 2006 and with the world pattern found by Mani (1964). This pattern of occurrence in the leaves happens because the leaves are abundant resources and constant (Maia 2001), besides having a continuous flow of nutrients needed for the maintenance of photosynthesis (Whitham 1978).…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…The gall inducers were not described and the galls have never been recorded again. The third cecidomyiid gall was described by Maia et al (2008) from São Paulo, Brazil, on Swartzia langsdorffii Raddi, being formed by the coalescence of two sides of a leaf. The cecidomyiid responsible for that gall is herein described.…”
Section: Introductionmentioning
confidence: 99%